PERTIMBANGAN HAKIM DALAM MENETAPKAN BESAR KECILNYA DENDA DALAM PERKARA ACARA CEPAT LALU LINTAS (STUDI KASUS DI PENGADILAN NEGERI PELALAWAN DAN SATUAN LALU LINTAS PELALAWAN) - YONA MELYSA; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Traffic problems, namely the human user, vehicle and road that interact in the movement of vehicles that meet the eligibility requirements driven by drivers follow traffic rules are set by traffic laws and road transport. With the number of traffic violations that occur in the region of Police law Pelalawan increasing. And the amount of fines set by a judge who does not comply with provisions of law rules applicable. The purpose of this thesis: First, to determine the application of sanctions against traffic violations that occurred in the jurisdiction of the Traffic Unit Pelalawan. Second, To know the basic consideration of the judge in determining the size of fines in the case of fast traffic events (a case study in the District Court Pelalawan and the Traffic Unit Pelalawan).This type of research is classified in socio-juridical kind of research, because the author directly conduct research at the locations studied. This research was conducted in the District Court Pelalawan and Traffic Unit Pelalawan, while population and sample, the whole party with regard to the issues examined in this study, the data source used primary data, secondary data, and the data tertiary, technical data collectors in research the Interviews and Literature Study.From the research problem there are two main things that can concluded. first, Whereas in the implementation of sanctions violations in the police resorts Pelalawan not in accordance with Law number 22 Year 2009 regarding Traffic and Road Transportation. The traffic police in carrying out his duties have not profesionall, namely the indiscriminate in enforcing the law. Lack of socialization traffic police to the public. The second implementation of the application of fines speeding ticket in court Pelalawan are not in accordance with the rule of law which is already regulated in Law Number 22 Year 2009 regarding Traffic and Road Transportation. Advice writer, first, It should further optimize the performance to reduce traffic violations in the region law police resorts Pelalawan, and the presence of a strong law enforcement in order to apply sanctions can give deterrent effect to offenders and can change the public's view of the image of the police, which many assume negative , And provide education to the public image of the law enforcement that have been adopted by law enforcement itself. Second, the judge should be able to carry out tasks and maintain an objective attitude in conducting the trial, and practice the ethics of the profession as well as possible, and do not abuse the profession in deciding a verdict in the trial.Keywords: Violation Penalties-Penalties-Traffic